Contribuição do Sistema Único de Saúde no rastreamento mamográfico do Brasil - Rodrigues, Danielle Cristina Netto (2017)
INTRODUCTION: In Brazil, access to mammography is performed by the Unified Health System (SUS) or by the Supplementary Health System, or by direct contracting of the individual with the health service. The SUS is the official system of government and came to meet constitutional law, which establishes that health is a right of all citizens and a duty of the State. OBJECTIVE: To evaluate the contribution of SUS to the mammographic screening of Brazil, in its macro-regions, Federal Units (UF) and Federal District (DF). METHOD: An ecological study where the information about breast cancer screening was analyzed through the mammograms performed, as well as the amount of equipment available for SUS in Brazil, in its macro regions, in the UF and DF, from 2008 to 2016 The study considered as target population, mammograms performed in women between the ages of 40 and 49 and between 50 and 69 years. Data on the production of exams were taken from the Outpatient Information System of the Department of Informatics of SUS (SIA / DATASUS), about the target population were extracted from the DATASUS Demographic and Socioeconomic Information System of Health and the Brazilian Institute of Geography and Statistics (IBGE), and on the equipment available for SUS, from the National Registry of Health Establishments (CNES). Based on this information, we evaluated the contribution of SUS to mammography screening in 2013, the temporal evolution of mammographic coverage during the period from 2008 to 2016, and the geographic evaluation of mammography access. RESULTS: The estimated mammographic coverage in the screening performed by SUS in Brazil in 2013 was 24.8%. The prevalence of mammograms ranged from 12.0% in the northern macroregion to 31.3% in the Southern Region. When stratified by UF, the lowest coverage was in Pará (7.5%) and the highest coverage was in Santa Catarina (35.7%). In Brazil, from 2008 to 2016, about 19 million mammograms were performed by the SUS in the female populationaged 50 to 69 years, costing approximately R$ 844 million. The Annual Percent Changes (APC) estimate allowed us to infer that mammographic coverage in Brazil increased in the period from 2008 to 2012 and stabilized in the following years. The Northeast macroregion was the only one that presented increased coverage throughout the studied period, while the South was the one that initially presented increase, with subsequent reduction. The North, Southeast and Midwest macro-regions showed increase, followed by a stabilization. Of the 26 UF, 31% (eight) showed a significant increase in mammographic screening coverage over the study period, 19% (five) presented APC stabilization, 46% (twelve) had an initial increase, and after that period, 92% (Eleven) stabilized and 0.8% (one) there was a reduction in coverage. Ceará presented initial stabilization, followed by an increase. The DF showed stabilization for an initial period and reduction after this period. In 2016, in Brazil, there were 4,628 mammographs. Of these, 4,492 (97%) were in use and 2,113 (47%) were available to perform tests for SUS. When considering the number of Mammograms (NM) necessary according to the indication of exams, it would be necessary for mammography screening in Brazil 2,068 devices. Regarding the production of examinations, the mammography network would be able to carry out 14,279,654 examinations and 4,073,079 were performed, equivalent to 29% of the total production capacity in the country in 2016. With regard to the maximum distance of 60km for It was verified that small areas of Brazil did not meet this indicator. CONCLUSION: The contribution of SUS to mammographic screening in Brazil is low and unequal, however, an increase has been occurring in recent years. The Brazilian population's access to mammographic screening is associated with insufficient production of mammographic network exams available for the SUS.